1988
DOI: 10.1093/treephys/4.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll and carotenoid concentrations in two varieties of Pinus ponderosa seedlings subjected to long-term elevated carbon dioxide

Abstract: Two varieties of ponderosa pine (Pinus ponderosa Dougl. var. scopulorum (Rocky Mountain variety) and P. ponderosa var. ponderosa (Sierran variety)) seedlings were subjected to elevated atmospheric CO(2) for two and a half years. The CO(2) concentrations were ambient, ambient + 75 microl l(-1), ambient + 150 microl l(-1) and ambient + 300 microl l(-1), or approximately 350, 425, 500 and 650 microl l(-1) CO(2). After one and a half years of exposure to elevated CO(2) and until the end of the study, seedlings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…It is notable that under field conditions at natural CO # -enriched sites, reductions in the soluble protein contents, which have frequently been reported in the leaves of plants grown in controlled CO # -enriched environments (Webber, Nie & Long, 1994) or decreases in photosynthetic pigments (Houpis et al, 1988 ;Wullschleger, Norby, & Hendrix, 1992 ;Tausz et al, 1996) were not found. A possible reason is that the trees grown at CO # springs have lower leaf area indices, show an accelerated growth only during first few years (Ha$ ttenschwiler et al, 1997) and, thus, might be able to maintain their nutrient balance.…”
Section: Co # Responses Versus Natural Variabilitymentioning
confidence: 85%
“…It is notable that under field conditions at natural CO # -enriched sites, reductions in the soluble protein contents, which have frequently been reported in the leaves of plants grown in controlled CO # -enriched environments (Webber, Nie & Long, 1994) or decreases in photosynthetic pigments (Houpis et al, 1988 ;Wullschleger, Norby, & Hendrix, 1992 ;Tausz et al, 1996) were not found. A possible reason is that the trees grown at CO # springs have lower leaf area indices, show an accelerated growth only during first few years (Ha$ ttenschwiler et al, 1997) and, thus, might be able to maintain their nutrient balance.…”
Section: Co # Responses Versus Natural Variabilitymentioning
confidence: 85%
“…The chlorophyll content was lower in elevated CO2, especially at higher PPFDs. Reductions in chlorophyll content at doubled atmospheric CO2 also occur for O. ficus-indica in open top chambers after 10 weeks (Cui et al 1993), for the CAM species Agave vilmoriniana after 2 weeks (Szarek et al 1987), for two tropical tree species after 2 to 4 months (Oberbauer, Strain & Fetcher 1985), for Liriodendron tulipifera and Quercus alba after 6 months (Wullsehleger, Norby & Hendrix 1992), and for Pinus ponderosa after 2-5 years (Houpis et al 1988). Starch accumulation in chloroplasts and reduced grana formation under elevated CO2 could be responsible for the decreased chlorophyll content (Wulff & Strain 1982;DeLucia era/.…”
Section: Discussionmentioning
confidence: 98%
“…chlorophyll and N contents, Rubisco activity, etc.) of leaf senescence (Miller et al, 1997;Sicher & Bunce, 1997;Houpis et al, 1988;Li et al, 2000), whereas, few studies report on the dynamic of leaf fall under elevated CO 2 (Gunderson et al, 1993), although several studies collected data on litter fall in FACE experiments (Allen et al, 2000;Finzi & Schlesinger, 2002;Norby et al, 2002). In any case, contrasting results were produced.…”
Section: Discussionmentioning
confidence: 99%